Diversidade de morcegos da família Phyllostomidae (Mammalia, Chiroptera) de ocorrência nos biomas brasileiros com foco na conservação - Lima, Amanda Cristiny da Silva (2021)
Bats belong to the order Chiroptera and have a high diversity, which makes this group an interesting object of study, especially in the area of animal systematics. The Phyllostomidae family stands out within the order as one of the most diverse, which makes the phylogenetic relationships of many of its taxons still uncertain. In addition, cryptic species and species complexes occur, which makes it difficult to identify the species for the family. In this context, the objective here was to identify and investigate the diversity of bats of the Phyllostomidae family (Mammalia, Chiroptera) that occur in the Amazon, Cerrado and Caatinga biomes of Brazil with a focus on conservation. For this purpose, specimens were collected in different biomes and in the laboratory of Genetics and Molecular Biology of UEMA, campus Caxias/MA, laboratory procedures were performed regarding morphological identification, as well as molecular techniques, making it possible to form a bank data with COI gene sequences produced in this laboratory and GenBank sequences. The results of the present study revealed the occurrence of a new record for the state of Maranhão, the species Sturnira tildae, which is presented in Chapter 2 of the dissertation. The identification, species diversity and conservation was the focus of chapter 3, in which 34 nominal species of the Phyllostomidae family were identified using morphological characters. C. brevicauda, M. schmidtorum, P. recifinus, P. fusciventris, R. fischerae and T. bidens were presented as complex taxa to be clarified. Several species delimitation tests were also used (ABGD, ASAP, bPTP and GMYC) which revealed 24 (ABGD) at 50 OTUs (ASAP, bPTP, sGMYC and mGMYC). A subdivision of at least two OTUs was found within 12 nominal species for the aforementioned tests indicating they are cryptic species. Regarding the conservation status, the diversity of registered species revealed that the species C. perspicillata, A. lituratus, A. planirostris and G. soricina were registered in the three studied biomes and denote that they are tolerant species to disturbed areas. S. lilium and D. rotundus were described from disturbed areas and were recorded in the Cerrado and Amazon. The species L. silvicola, L. brasiliense were recorded in the Cerrado biome and D. ecaudata in the Caatinga, these species are more sensitive to environmental changes, being found in preserved areas. The species C. brevicauda, A. fimbriatus, A. obscurus, P. discolor have also been described for anthropized or disturbed areas. This study also presents the bats that occur in the Cerrado and Amazon biomes, which is discussed in chapter 4.